Thrust - Yuknavitch, Lidia (Riverhead Books, 2022)
"From the visionary author of The Book of Joan and The Small Backs of Children, an epic novel tracing the conception and construction of a colossal statue--and the lives of two centuries of immigrants navigating its turbulent wake. "Lidia Yuknavitch is a writer who, with each ever more triumphant book, creates a new language with which she writes the audacious stories only she can tell," Roxane Gay has written. Now, Yuknavitch bridges the nineteenth and late twenty-first centuries with an imaginative masterpiece: the story of the life and afterlife of a national monument to liberty, as told through the lives of those who built it and those who struggle to survive in its imperfect shadow. Through three braided storylines, we follow the sculptor Frédéric and his firebrand American lover, Aurora; Mikael, an Eastern European orphan locked in an American prison, and Lilly, a case worker trying to save him; and the construction worker Aster and his daughter Laisvė, a "carrier" with a gift of using ancient waterways to swim through time. As the dream Frédéric conceived--and Aster helped build--founders under rising seas, Laisvė must dodge enforcement raids and find her way back to Lilly and then, finally, to Aurora, to forge a connection that might save their fractured dream of freedom"--